Controlling cassava mosaic virus and cassava mealybug in Sub-Saharan Africa - Nweke, Felix I. (International Food Policy Research Institute, 2009)
Cassava was imported from Latin America some 300 years ago, and colonial governments in Africa used it as a famine-reserve crop. Over time cassava spread to over 40 countries in Sub-Sahara Africa, and Nigeria is now the largest cassava producer in the world. At Africa's independence in the 1960s, cassava mosaic disease was a major problem. In the 1970s, the cassava mealybug appeared and threatened to decimate the African cassava industry. Cassava mosaic and mealybug control programs were introduced in the 1970s to combat these two problems. The International Institute of Tropical Agriculture (IITA) drew on research on mosaic disease control in Tanzania and developed high-yielding mosaic disease resistant Tropical Manioc Selection (TMS) varieties in only six years of research, from 1971 to 1977. The TMS varieties increased cassava yields by 40 percent without fertilizer. To tackle the mealybug problem, an Africa-wide biological control center was established at the IITA in Nigeria. The IITA brought together an international group of scientists and donors who crisscrossed Central and South America and eventually found a wasp that fed off the mealybug. The wasp was imported from South America into Africa and introduced into cassava fields in over 100 locations throughout Sub-Saharan Africa. The wasp has been effective in bringing the mealybug under control and reduces yield loss by 2.5 tons per hectare. The successful control of both the cassava mosaic disease and the cassava mealybug problems has raised cassava yields and turned cassava into a cash crop that is now spreading throughout Africa. Both cassava success stories are an example of the payoff from problem-solving research that may take many decades.